Pilot scale microwave sorting of porphyry copper ores: Part 1: laboratory investigations - Batchelor, A.R.; Ferrari-John, R.S.; Katrib, Juliano; Udoudo, O.B.; Jones, D.A.; Dodds, Chris; Kingman, S.W. (Elsevier, 2016)
Microwave treatment followed by infrared thermal imaging (MW–IRT) has been proposed as a potential excitation-discrimination technique to facilitate sorting of porphyry copper ores. A continuous, high throughput (up to 100t/h), belt–based microwave cavity operating at up to 100kW has been designed to interface directly with commercially available sorters at industrially relevant scales. In this paper, the fragment-by-fragment thermal response of 16 porphyry copper ore samples following microwave treatment in the bespoke system is evaluated to elucidate key performance criteria and identify likely candidate ores for microwave sorting. Microwave treatment energy dose was found to be the driving force behind the ultimate average temperature fragments experience, with other process variables (e.g. belt speed, power, belt mass loading, thermal equilibration time) having little effect on sortability performance. While fragment mineralogical texture and ore textural heterogeneity were shown to influence the average temperature rise of the fragment surface presented to the thermal camera, in most cases this variability did not adversely affect sortability performance. An abundance of microwave-heating gangue minerals (e.g. iron sulphides, iron oxides and hydrated clays) was shown to be the dominant source of deviation from intrinsic sortability. However, low average moisture content and co-mineralisation of copper and iron sulphides (or bulk sulphide sorting) was found to mitigate the deviation and provide better sortability performance. An attractive separation could be proposed for many of the ores tested, either to remove a large proportion of barren fragments from ore-grade material or concentrate a large proportion of copper values from waste-grade material.